METHODOLOGICAL APPROACHES TO DESIGNING ENGLISH LESSON PLANS (Web of Teachers: Inderscience Research, 2025)
In the modern world, English language instruction has become a vital part of education at all levels. The growing demand for English proficiency in academic, professional, and social settings necessitates well-organized, methodologically sound lesson plans that cater to diverse learners’ needs. Designing effective lesson plans for English classes requires a deep understanding of methodological approaches that address various learning theories, pedagogical goals, and classroom realities.